Idiopathic Splenic Artery Pseudoaneurysm Successfully Treated with Embolization - Dias, João Lopes (2014)
Splenic artery pseudoaneurysms are rare and typically resultant from pancreatitis, spleen trauma, and iatrogenic complications. Unlike true aneurysms, pseudoaneurysms are usually symptomatic and more prone to rupture. We report the case of an asymptomatic, idiopathic splenic artery pseudoaneurysm in a 84-year-old woman that underwent an abdominal computed tomography (CT) examination after the inaugural diagnosis of diabetes mellitus. No prior history of pancreatitis, trauma or abdominal surgery was documented. Attending to the unpredictable risk of rupture, splenic artery embolization was performed with no immediate complications. One month after the procedure, a follow-up Doppler ultrasound found no flow inside the pseudoaneurysm.